Peran Perilaku Keuangan dan Nilai Gontori Dalam Mendorong Kesuksesan Alumni Santri Berwirausaha - Rahmanto, Dhidhin Noer Ady (JESI (Jurnal Ekonomi Syariah Indonesia), 2024)
This study delves into the key factors contributing to success in the business world, particularly among pesantren alumni in Indonesia. Purpose; It focuses on identifying and analyzing the influence of financial behavior and Gontor values, including the Panca Jiwa principles (the spirit of sincerity, the soul of simplicity, the soul of self-reliance, the soul of Ukhuwah Islāmiyah, and the soul of freedom), on financial decision-making and actions of alumni within their business contexts. Method; Employing a mixed-method approach with a concurrent triangulation design, it combines qualitative and quantitative analyses. For the qualitative part, purposive sampling was used, selecting several successful entrepreneur alumni from Yogyakarta, Solo, and Ponorogo, totaling about 10 respondents. The quantitative portion of this study involved 147 respondents, chosen through simple random sampling from the population of entrepreneurial alumni. Results; The findings indicate that the majority of respondents have experienced positive development in their businesses, with increased or stable income. This is supported by a strong commitment to business ethics, prudent and controlled decision-making, and integrity in transactions and financial reporting. An approach based on analysis and avoidance of impulsive decisions indicates maturity in business strategy. Conclusion; These findings emphasize that success in entrepreneurship is not solely measured by financial growth, but also by the application of ethical values, integrity, and responsibility in business management. Future research could investigate how financial education and entrepreneurial skill development can be more effectively integrated into the pesantren curriculum to prepare more resilient future entrepreneurs.